Design and Characterization of Letrozole Ethosomes for Improved Topical Treatment of Breast Cancer - Harale, Swapnil; Kadam, Aviraj; Galatage, Sunil; Manjappa, Arehalli; Katkar, Rushikesh; Shinde, Sumit; Alman, Abhinandan A; Kumbhar, Prajyot; Bille, Kranti; Kadam, Rahul; Kandukuri, Gourisankar (Indian Journal of Pharmaceutical Education and Research, 2025)
Background: Breast cancer is the leading and most frequent cancer among women worldwide, with rapidly growing new cases diagnosed, surpassing lung cancer. The current study aims to design, optimize and characterize Letrozole (LTZ) Loaded Ethosomes (LTZ-ETH) for the treatment of breast cancer. Materials and Methods: Ethosomes were optimized using a two-factor, three-level (32) factorial design technique. The ethosomes were characterized by vesicle size, zeta potential and entrapment efficiency. The optimized LTZ-ETH was tested for surface morphology and in vitro cytotoxicity. Results: The optimized LTZ-ETH has flawed round-shaped unilamellar structures with an average vesicle size of 218.6 ± 5 nm and an entrapment efficiency of 92.45±3.42%. Optimized LTZ-ETH demonstrated significant (p<0.01) in vitro cytotoxicity (IC50: 23.27±1.48 µg/mL) than LTZ (58.70±2.46 µg/mL) against MCF-7 Cells. Compared to LTZ, LTZ-ETH treatment caused apoptosis of large proportion of cancer cells. The above results could be correlated to the increased cell uptake of LTZ-ETH as shown by in vitro cell uptake study. Furthermore, the in vitro skin permeation study results revealed enhanced penetration of LTZ-ETH into the deeper layers of the skin. Conclusion: The study results revealed that LTZ-ETH could be used as a potential alternative treatment approach to conventional chemotherapy. However; further in vivo animal studies are required to establish its efficacy in the treatment of breast cancer.
Keywords: Apoptosis; Breast Cancer; Ethosomes; Factorial Design; Letrozole; Optimization